Walking with Henry : big lessons from a little donkey on faith, friendship, and finding your path - Ridge, Rachel Anne (Tyndale Momentum, the nonfiction imprint of Tyndale House Publishers, Inc., 2019)
Sometimes it arrives as a moment of joy in the middle of despair. Sometimes you find it next to a trusted friend along an old, well-trodden path. And sometimes, grace has fuzzy ears, a bristled mane, and hope for a new start. Join Rachel Anne Ridge, author of the beloved memoir Flash, in a journey back to the pasture. As she adopts a second rescue donkey as a little brother for Flash<U+2015>a miniature named Henry<U+2015>she finds that walking with donkeys has surprising lessons to teach us about prayer, renewing our faith, and connecting to God in fresh ways.